Comparison of two systemic antifungal agents, itraconazole and terbinafine, for the treatment of dermatophytosis in European hedgehogs (Erinaceus europaeus). Issue 6 (12th September 2016) - Bexton, Steve; Nelson, Helen
Abstract : Background: Dermatophytosis caused by Trichophyton erinacei is a common scaling and crusting skin disease affecting European hedgehogs ( Erinaceus europaeus ) admitted to wildlife rescue centres. The application of topical therapy can be challenging because wild hedgehogs are subject to stress and often roll into a ball when handled. Systemic antifungal therapy is more convenient but has not been evaluated in this species. Hypothesis/Objectives: To compare the efficacy of oral itraconazole versus oral terbinafine for the treatment of dermatophytosis affecting hedgehogs. Animals: A treatment trial was undertaken in a wildlife hospital involving 165 hedgehogs with naturally occurring dermatophytosis. Methods: Animals were randomly divided into two groups and treated with either itraconazole or terbinafine orally for 28 days. The therapeutic efficacy was evaluated after 14 and 28 days by mycological culture and clinical dermatological lesion scores. Results: Both drugs were well tolerated and clinically effective. After 14 and 28 days of treatment, the respective mycological cure rate was 36.6% and 65.9% for the itraconazole‐treated group and 92.8% and 98.8% for the terbinafine‐treated group. Conclusion and clinical importance: Itraconazole and terbinafine were both effective for the treatment of dermatophytosis affecting hedgehogs; however, terbinafine was more effective. Abstract : Background –Dermatophytosis caused by Trichophyton erinacei is a common scaling and crusting skin disease affecting European hedgehogs ( Erinaceus europaeus ) admitted to wildlife rescue centres. The application of topical therapy can be challenging because wild hedgehogs are subject to stress and often roll into a ball when handled. Systemic antifungal therapy is more convenient but has not been evaluated in this species.Hypothesis/Objectives –To compare the efficacy of oral itraconazole versus oral terbinafine used for the treatment of dermatophytosis affecting hedgehogs.Conclusion and clinical importance –Itraconazole and terbinafine were both effective for the treatment of dermatophytosis affecting hedgehogs; however, terbinafine was more effective.